'Familiar friends': Catholic mother–daughter narratives. Issue 4 (1st October 2016) - Keary, Anne
Abstract: The main theoretical and practical focus of this paper is on the Catholic mother–daughter relationship, and how connections between women shape, and are shaped in, and through this nexus. It is contended that it is imperative that we begin to understand different representations of connections among, and between women, including that of mothers and daughters, as they compose part of the changing yet continual dialect of our (religious) feminine identities. The intent is to embrace the contradictions and polarities, which are apparent in these inter-generational relations. This article is set in middle class suburban Melbourne Australia, and spans the period from the early to late twentieth century. Conversations between an Anglo-Saxon Catholic mother and daughter act as a catalyst to discuss the matrilineal pedagogical dimensions that mark female relations within social and religious discourses.